Efficacy and safety of an inhaled pan-Janus kinase inhibitor, nezulcitinib, in hospitalised patients with COVID-19: results from a phase 2 clinical trial - Tuan Nguyen; Jacky Woo; Rajeev Saggar; Nathan D Pfeifer; David A Lombardi; Brett Haumann; John Belperio; Maxim Bogus; Valentyn Moskalenko; David L Bourdet; Elad Kaufman; Corbin G Thompson; et al. (BMJ Open Respiratory Research)
Background The inhaled lung-selective pan-Janus kinase inhibitor nezulcitinib had favourable safety and potential efficacy signals in part 1 of a phase 2 trial in patients with severe COVID-19, supporting progression to part 2.Methods Part 2 was a randomised, double-blind phase 2 study (NCT04402866). Hospitalised patients aged 18–80 years with confirmed symptomatic COVID-19 requiring supplemental oxygen (excluding baseline invasive mechanical ventilation) were randomised 1:1 to nebulised nezulcitinib 3 mg or placebo for up to 7 days with background standard-of-care therapy (including corticosteroids). Efficacy endpoints included respiratory failure-free (RFF) days through day 28 as the primary endpoint. Secondary endpoints included safety and change from baseline oxygen saturation (SaO2)/fraction of inspired oxygen (FiO2) ratio on day 7, and 28-day mortality rate was a prespecified exploratory endpoint.Results Between June 2020 and April 2021, 205 patients were treated (nezulcitinib, 103; placebo, 102). There was no statistically significant difference between nezulcitinib versus placebo in the primary endpoint (RFF days; median, 21.0 vs 21.0; p=0.6137) or secondary efficacy endpoints. Nezulcitinib was generally well tolerated with a favourable safety profile.Conclusions Although the prespecified primary, secondary and exploratory efficacy endpoints, including RFF through day 28, change from baseline SaO2/FiO2 ratio on day 7, and 28-day mortality rate, were not met, nezulcitinib was generally well tolerated and had a favourable safety profile. Further studies are required to determine if treatment with nezulcitinib confers clinical benefit in specific inflammatory biomarker-defined populations of patients with COVID-19.